(untitled) (Linguist, 2021)
The Discourse-Historical Approach is one of two versions of Critical Discourse Analysis (CDA) with a strong and organized focus on argumentation. The second version is that developed by Isabela Ieţcu-Fairclough and Norman Fairclough (see, e. g. , Ieţcu, 2006a, 2006b; Ieţcu-Fairclough, 2007; Fairclough and Fairclough, 2010, 2012, 2013) . The following chapter will only focus on the Discourse-Historical Approach to the critical analysis of argumentation. It will outline basic conceptual and methodological assumptions about the nature of argumentation and the relationship between argumentation analysis and the Discourse-Historical Approach. The main ideas to be presented and explained in the following have been clear for many years, but it is the first time that they are summarized for the English language readership. There is an urgency to explain them in English, because there circulate several misunderstandings in the English-speaking scientific community of critical discourse analysts with respect to the relationship between argumentation.